Togo : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper (2009-11). (IMF Staff Country Reports; Country Report, 2010)
The Poverty Reduction Strategy Paper for Togo builds on the strategy laid out in the Interim Strategy for Poverty Reduction (I-PRSP). Owing to circumstances largely beyond the control of the authorities, the results obtained under the implementation of the I-PRSP have been below expectations. The hike in oil and food prices and the severe flooding in 2008, and the global recession in 2009 have adversely impacted the performance of the Togolese economy, dragging down growth just as it has been poised to improve in response to the economic program.